Technology of Internet of Things Responding to Natural Disasters - Chen, Shu-Wen; Shao, Jia-Qi; Zhu, Hui-Sheng (EAI Endorsed Transactions on Internet of Things, 2021)
Numerous countries have been affected by natural disasters, the seriousness of which consequences is self-evident, such as power failure, building collapse and communication interruption. With the rapid development of science and technology, the Internet of Things (IoT) has become one of the most important part of current information technology. More and more countries and regions have realized the significance of IoT in dealing with natural disasters and are making efforts to put IoT into use. This paper summarizes the latest progress of IoT with fog computing, swarm robots and other advanced technologies in coping with natural disasters on four aspects. It focuses on how the IoT and other information technologies can solve problems encountered in natural disasters to a certain extent.